2011
DOI: 10.1093/nar/gkr232
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-192 targeting retinoblastoma 1 inhibits cell proliferation and induces cell apoptosis in lung cancer cells

Abstract: microRNAs play an important roles in cell growth, differentiation, proliferation and apoptosis. They can function either as tumor suppressors or oncogenes. We found that the overexpression of miR-192 inhibited cell proliferation in A549, H460 and 95D cells, and inhibited tumorigenesis in a nude mouse model. Both caspase-7 and the PARP protein were activated by the overexpression of miR-192, thus suggesting that miR-192 induces cell apoptosis through the caspase pathway. Further studies showed that retinoblasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 41 publications
(60 reference statements)
8
96
3
2
Order By: Relevance
“…Song et al (18) also found that miR-192 overexpression suppresses cell proliferation in colon cancer cell lines through induction of p53-dependent cell cycle arrest at both the G1 and G2 phases. In lung cancer cells, miR-192 was found to inhibit cell proliferation through targeting RB1 (19). Our results are highly inconsistent with these previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Song et al (18) also found that miR-192 overexpression suppresses cell proliferation in colon cancer cell lines through induction of p53-dependent cell cycle arrest at both the G1 and G2 phases. In lung cancer cells, miR-192 was found to inhibit cell proliferation through targeting RB1 (19). Our results are highly inconsistent with these previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The growth-promoting effects of miR-192 overexpression were also observed in the in vitro colony formation assay and in vivo xenograft tumor model. This inconsistency with previous reports (18,19,23) may reflect the effects on the functional consequences of manipulating miRNA. Similar to miR-192, miR-17-5p is able to act as both an oncogene and a tumor suppressor in different types of cancer cells (24).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…39 Thus, further studies are required to elucidate the role of this miRNA family in thyroid tumorigenesis. However, the tumor suppressive role of miR-192 has been robustly functionally demonstrated, [40][41][42] and is consistent with our current observation. In this regard, the value of the tumor set 2 was limited for validation, as the time of follow-up was shorter.…”
Section: Modern Pathology (2015) 28 748-757supporting
confidence: 93%
“…This positive feedback loop TP53-miR-192/194-MDM2 confers the status of tumor suppressor to the miR-192/194 cluster. Recently, the importance of this circuit has been further strengthened by the identification of new oncogenes among the downregulated target genes of these miRNAs (14,28,29). In our analysis, PSME3 and CUL4A are promising miR-192/194 targets, being among the miR-194 anticorrelated predicted target genes and proteins that physically associate with MDM2 and part of the TP53 degradation pathway.…”
Section: Mucinous Subtype Markers: Mir-192 and Mir-194mentioning
confidence: 76%